2011
DOI: 10.1186/1475-2875-10-265
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mosquito net use in Ghana

Abstract: BackgroundDuring the past decade the malaria control community has been successful in dramatically increasing the number of households that own mosquito nets. However, as many as half of nets already in households go unused. This study examines the factors associated with use of nets owned in Ghana.MethodsThe data come from an August 2008 survey in Ghana of households with a pregnant woman or a guardian of a child under five, conducted during the rainy season. 1796 households were included in this analysis, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
56
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 24 publications
21
56
3
Order By: Relevance
“…Some studies have shown that a personal decision to purchase a net may motivate one to use the ITNs [16] rather than getting it for free. Therefore it is important to encourage commercial distribution of ITNs but at a subsidized price that is at the barest minimum [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that a personal decision to purchase a net may motivate one to use the ITNs [16] rather than getting it for free. Therefore it is important to encourage commercial distribution of ITNs but at a subsidized price that is at the barest minimum [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, access does not always result in usage due to sociocultural and logistical reasons [15]. Evidence from some parts of Ghana has shown that over 40% of ITNs available in the households go unused [16]. This could erode the gains made in ITN use over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Education and occupation had an influence in vector control tools, therefore, knowledge and utility might have more impact on bed net effect for wide community protection either provided for free or under subsidized price [35,69,70]. In malaria-endemic parts of western Kenya and Ghana, studies have found that, the nets offered to pregnant mothers and infants during clinics visits do not mean utility for personal protection as many people own bed nets but do not use them [35,71]. …”
Section: Discussionmentioning
confidence: 99%
“…This is critical for malaria transmission, given that radio programmes have assisted policy makers to identify critical channels for net utilization and compliance with safe practices in order to avoid being bitten by mosquitoes. In Cameroon, the impact of "KO Palu" which means "Knock Out Malaria" campaign was investigated and found to positively influence compliance with mosquito net usage and reduction of malaria episodes [9,41,42].…”
Section: Maternal Socio-economic Status and The Incidence Of Malaria mentioning
confidence: 99%